(untitled) (Educational Perspectives Magazine (REPED), 2023)
This article describes a visión to work the conflicts in the school in context of a world in mutation, which prints new challenges to the teachers among them to teach to its students lo be better people and to coexist in a competitive and exhausting system. Since the paradigm of complexity is presented as a positive Conflictology treatment conflicts without addressing pedagogically hide "under the carpet" as is the case in most of our classrooms.